2007
DOI: 10.1016/j.jfms.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A case of feline leprosy caused by Mycobacterium lepraemurium originating from the island of Kythira (Greece): diagnosis and treatment

Abstract: A 2-year-old, 4 kg, healthy, domestic shorthair female cat presented with ulcerated subcutaneous nodules on the commissures of its mouth. The cat was negative for feline leukaemia virus and feline immunodeficiency virus. Skin mycobacteriosis was diagnosed after detection of numerous acid-fast bacilli in Ziehl Neelsen-stained smears from the ulcers. Feline leprosy was suspected following preliminary polymerase chain reaction results: positive for Mycobacterium genus but negative for Mycobacterium tuberculosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…rats or possums. Mycobacterial species associated with feline leprosy include Mycobacterium lepraemurium (Figure 3), 18,19 Mycobacterium visibile, 11 Mycobacterium sp. strain Tarwin (Figure 4) 9 and a novel species found in New Zealand and the East coast of Australia.…”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…rats or possums. Mycobacterial species associated with feline leprosy include Mycobacterium lepraemurium (Figure 3), 18,19 Mycobacterium visibile, 11 Mycobacterium sp. strain Tarwin (Figure 4) 9 and a novel species found in New Zealand and the East coast of Australia.…”
Section: Aetiologymentioning
confidence: 99%
“…Mycobacterium lepraemurium infections have been reported from the UK, the Netherlands, France, Greece, Australia, New Zealand the USA (including the island of Hawaii). 18,19 The development of disease is due to a complex and incompletely understood interaction between the organism and the immune response of the host. Some organisms (e.g.…”
Section: Aetiologymentioning
confidence: 99%
“…Gingiva, nasal plane and internal organs may also be involved. The condition occurs in temperate, coastal climates and has been reported in New Zealand, 6,7 Australia, 8–10 Western Canada, 11,12 the Netherlands, 13 UK 14,15 USA, 16 North Italy, 17 and Greece 18 . The causative agent is presumed to be M. lepraemurium ; however, recent studies using the polymerase chain reaction (PCR) have recently demonstrated the presence of other mycobacteria including novel species 9,10,19,20 …”
Section: Introductionmentioning
confidence: 99%
“…Treatment failure or lesion recurrence can occur because of either an inappropriate or insufficient course of systemic antimicrobial therapy, or incomplete surgical excision. 3 Clofazimine is generally well tolerated in cats, 18,22 but was not readily available at the time we encountered this case. In this case, the lesion was focal, although the presence of a small satellite lesion adjacent to the primary nodule suggested sporotrichoid spread via regional lymphatics may have already occurred.…”
Section: Discussionmentioning
confidence: 98%
“…may influence the species of Mycobacterium involved in disease. 3,6,18 Case report A 5-year-old spayed female Domestic Shorthair-cross (4.6 kg) originating from the Central Coast region of NSW was presented for examination of a raised, alopecic skin nodule that had developed rapidly on the external surface of the right upper lip, immediately caudal to the middle row of whiskers. 1,2,6,15 Within Australia, M. sp.…”
mentioning
confidence: 99%